Peran Masyarakat Nelayan Pada Peningkatan Motivasi Belajar Siswa Mata Pelajaran Ips Kelas Viii Masa Covid-19 Di Mts Muhammadiyah Al-Fatah Nangahale - SUMAIA; Mohammad Amir; Mohammad Fitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development in the study raised the question of the role of fishermen to the pouingtivas of niill class VIII subjects at the time MTs Muhammadiyah Al-fatah Nangahale . The goal to achieve and the research is to learb about the role communities at the covid-19, study of the IPS of the class VIII from the covid-19, the study IPS a qualitative desktop approach. Tekmike compiles the data used this research-engineering, observast, interview and documentation. The results of the study is to boring to the public an effort to prevent children from being cut children in spite of the covid-19 clinical conditions, agains the promise of children at home by creating a schedule that allows the study of anals to be controlled by the society, agains the protection of the childs experience in order to motivate childrens performance in learning, peopke have always been supportive and supportive of their childs achievement in learning.